2018
DOI: 10.3390/atmos9090333
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas Fugitive Leak Detection Using an Unmanned Aerial Vehicle: Localization and Quantification of Emission Rate

Abstract: We describe a set of methods for locating and quantifying natural gas leaks using a small unmanned aerial system equipped with a path-integrated methane sensor. The algorithms are developed as part of a system to enable the continuous monitoring of methane, supported by a series of over 200 methane release trials covering 51 release location and flow rate combinations. The system was found throughout the trials to reliably distinguish between cases with and without a methane release down to 2 standard cubic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 24 publications
1
62
0
Order By: Relevance
“…Accurate top-down flux quantification from facility-scale sources requires a combination of wind vector measurements along with in situ measurements of atmospheric methane mole fraction (Dlugokencky et al, 1994;Rigby et al, 2017). Facility-scale emission fluxes can be derived from near-field sampling (less than 500 m from the source), which may be acquired from an unmanned-aerial-vehicle (UAV) platform (Gottwald and Tedders, 1985). UAVs are cheap, versatile and relatively easy to use (Villa et al, 2016) compared to large, manned aircraft (Illingworth et al, 2014;Lehmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate top-down flux quantification from facility-scale sources requires a combination of wind vector measurements along with in situ measurements of atmospheric methane mole fraction (Dlugokencky et al, 1994;Rigby et al, 2017). Facility-scale emission fluxes can be derived from near-field sampling (less than 500 m from the source), which may be acquired from an unmanned-aerial-vehicle (UAV) platform (Gottwald and Tedders, 1985). UAVs are cheap, versatile and relatively easy to use (Villa et al, 2016) compared to large, manned aircraft (Illingworth et al, 2014;Lehmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have used UAV remote-sensing measurements to derive emission fluxes (Golston et al, 2018;Yang et al, 2018). However, to our knowledge, only Nathan et al (2015) have derived fugitive methane emission fluxes using UAV in situ measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Barchyn et al (2019) tested a leak detection algorithm, by flying in single transects downwind of a controlled release, measuring in situ methane mole fraction with ±0.05 ppm precision. Golston et al (2018) sampled at a fixed height above a controlled release, using remote sensing methane measurements in equally sized grid squares, to identify and quantify emissions using mass balance box modelling. Yang et al (2018) flew in circles around the rough location of a controlled release and used remote sensing measurements to identify the source location and quantify emissions, using mass balance box modelling.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to have some estimates of methane emission from natural gas extraction in hand as natural gas extraction contains a range of leaks which is varying in levels, from very low to high . Alvarez et al found that in USA emission of methane only in natural gas production is 7.6 Tg/y and total process emission of methane in natural gas industry is 13 Tg/y, which is 60% more than EPA standard. Significant gap in technology is found to be one of the important concerns in identification and mitigation of methane leakage from natural gas field…”
Section: Natural Gas As a Transitional Fuel: The Conceptmentioning
confidence: 99%